High-valent nickel complexes supported by pyridinedicarboxamidate ligands in hydrocarbon oxidation reactions - Pirovano, Paolo (Trinity College Dublin. School of Chemistry. Discipline of Chemistry, 2017)
High-valent M=O and M-O-X complexes are hypothesised to be potent oxidising intermediates both in enzymatic and small-molecule catalysis. In contrast to those from groups 6-8, oxidants that contain late transition metals (Co, Ni, Cu) are poorly understood. Because of their high reactivity, only a few examples of these compounds have been observed. We have investigated complexes of these metals supported by the dianionic pyridinedicarboxamidate pincer ligands (pyN2Me2 and pyN2iPr2). In particular, we have prepared a series of [NiII(L)(pyN2Me2)] complexes, which were successively oxidised, at low temperature to generate metastable [NiIII(L)(pyN2Me2)] species. These NiIII complexes were characterised by UV-Vis, EPR and XAS spectroscopies, and DFT computations. We probed their oxidising power in reactions with phenols (O-H oxidation) and hydrocarbon substrates (C-H oxidation). The NiIII-OAc species oxidised hydrocarbon substrates with a wide range of C-H bond dissociation energies, from xanthene (BDEC-H = 75.5 kcal/mol) to toluene (BDEC-H= 89 kcal/mol). Kinetic analysis of the reactions revealed them to proceed through a hydrogen atom abstraction mechanism, as evidenced by primary D/H kinetic isotope effects (3.0-3.3) and a linear relationship between reaction rates and the BDEC-H of substrates (Bell-Evans-Polanyi relationship). In terms of reaction rates, NiIII-OAc was shown to be a very powerful oxidising agent, greatly surpassing FeIII-O-X and MnIII-O-X species and rivalling the best hydrogen atom abstractors such as FeIV=O and CuIII-OH compounds. We also obtained indirect evidence for the existence of a transient, highly reactive intermediate, in the reaction of a [NiII(CH3CN)(pyN2iPr2)] precursor with m-CPBA. We observed the formation of decay products, which together with isotopic labelling experiments and DFT calculations, formed proof for the formation of the NiIII-O? species. The main ligand degradation product was an unusual benzoxazine, which derived from hydro- gen atom abstraction from a benzylic C?H group of the supporting ligand. In the final part of the thesis, we began to explore the coordination of pyN2iPr2 to other first row transition metals, in view of probing the effect of varying d electron count and electronegativity on the oxidising reactivity of M-O-X complexes. In particular, we have synthesised and characterised [CoII(CH3CN)(pyN2iPr2)], which will serve as the precursor for high valent oxidants, as well as zinc complexes [ZnII(OAc)(pyN2iPr2)]- and [ZnII(Br)2(HpyN2iPr2)]- .
APPROVED
Keywords: Nickel complexes; Hydrocarbon oxidation; Reactive Intermediates; Bioinorganic chemistry; Metal oxo complexes